Electrochemical properties of lithium–titanium oxide, modified with Ag–Cu particles, as a negative electrode for lithium-ion batteries. Issue 82 (9th November 2017) - Krajewski, Michal; Hamankiewicz, Bartosz; Michalska, Monika; Andrzejczuk, Mariusz; Lipinska, Ludwika; Czerwinski, Andrzej
Abstract : Composites of Li4 Ti5 O12 with Ag–Cu particles were successfully synthesized by solid-state reaction followed by thermal decomposition of the metal substrates. Abstract : Composites of Li4 Ti5 O12 with Ag–Cu particles were successfully synthesized by solid-state reaction followed by thermal decomposition of the metal substrates. The presence of metallic particles was confirmed by X-ray diffraction, scanning transmission electron microscopy and X-ray photoelectron spectroscopy. Galvanostatic charge–discharge tests showed improved specific capacity and capacity retention of Li4 Ti5 O12 /Ag–Cu composites at a 10C current rate, while cyclic voltammetry and electrochemical impedance spectroscopy revealed changes in Li + ion chemical diffusion coefficient values and charge-transfer resistance with increasing amount of Ag–Cu in prepared powders. The synthesis and structural, morphological and electrochemical evaluation of Li4 Ti5 O12 /Ag–Cu powders, carried out in this work, were also presented here for the first time.